Beyond Doctrinal Boundaries: A Maqāṣid-Based Approach to Religious Moderation in the Qur’anic Narrative of Prophet Abraham - Ach. Maimun; Fathurrosyid; A. Tajib (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2024)
The dissemination of religious moderation through various currents of thought continues to evolve, as evidenced by the increasing number of academic publications discussing religious moderation from diverse perspectives. However, while academic research has succeeded in enhancing public understanding, the literature often focuses more on verses pertaining to aḥkām, neglecting the study of religious moderation based on narrative verses in the Qur’an, which serve as a role models for expressing religion in a moderate manner. This research emphasizes the reasoning behind religious moderation based on the story of Abraham in the Qur’an, analyzed through the lens of the Islamic trilogy. Utilizing literature data and the theory of maqāṣidī interpretation, this paper identifies three models of religious moderation exemplified by Prophet Abraham according to the Islamic trilogy: First, the dimension of faith, which involves understanding and strengthening the prominence of monotheism through correct and proper religious comprehension. Second, the dimension of Sharia, which narrates values aimed at upholding humanity and welfare. Third, the dimension of morality, which emphasizes the importance of peaceful preaching to foster harmony in religious diversity and plurality.